2020
DOI: 10.3390/ijms21041179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxic Amyloid β42 Oligomers in Rat Primary Cerebral Cortex Cells and Human iPS-derived Neurons Treated with 10-Me-Aplog-1, a New PKC Activator

Abstract: Amyloid β42 (Aβ42), a causative agent of Alzheimer's disease (AD), is derived extracellularly from Aβ precursor protein (APP) following the latter's cleavage by β-secretase, but not α-secretase. Protein kinase Cα (PKCα) activation is known to increase α-secretase activity, thereby suppressing Aβ production. Since Aβ42 oligomer formation causes potent neurotoxicity, APP modulation by PKC ligands is a promising strategy for AD treatment. Although bryostatin-1 (bryo-1) is a leading compound for this strategy, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…PKCα belongs to the serine/threonine kinases family, and its signal transduction is mediated by calcium and diacylglycerol as second messengers ( Newton, 2010 ). It has been demonstrated that the activation of PKCα could elevate α-secretase activity that inhibits Aβ production ( Murakami et al, 2020 ). In the present study, we also observed that PKCα expression level is significantly increased in the thymol and carvacrol groups compared to Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…PKCα belongs to the serine/threonine kinases family, and its signal transduction is mediated by calcium and diacylglycerol as second messengers ( Newton, 2010 ). It has been demonstrated that the activation of PKCα could elevate α-secretase activity that inhibits Aβ production ( Murakami et al, 2020 ). In the present study, we also observed that PKCα expression level is significantly increased in the thymol and carvacrol groups compared to Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue also includes papers that addressed the preventive and/or therapeutic potentials of chemical compounds or drugs for Aβ-related neurodegenerative diseases. Murakami et al, who focused on 10-Me-Aplog-1, a new protein kinase C activator, demonstrated its inhibitory effects on the intracellular formation of toxic Aβ oligomers in rat primary cerebral cortex cells [ 7 ]. In a mouse model of cerebral amyloid angiopathy, Yakushiji et al showed that the administration of low-dose phosphodiesterase III inhibitor cilostazol improved vascular deposition of Aβ, potentially by facilitating perivascular drainage of Aβ [ 8 ].…”
mentioning
confidence: 99%